Operative Anatomy of the Heart - Berdajs, Denis; Turina, Marko I.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Operative Anatomy of the Heart covers unique data and artwork on the morphological description of cardiovascular surgery and surgical procedure. Topics covered include the entire anatomy of the human chest. An appendix presents the cross sections of the human body including the thoracic, abdominal and pelvic cavity. These sections are presented as morphological guidelines for better interpretation of the computer scans.
Thorac Regions -- Surgical Approaches -- Coronary Bypass Grafts -- Coronary Arteries -- Aortic Valve -- Mitral Valve -- Pulmonary Valve -- Tricuspid Valve -- The Interventricular Septum -- Heart Conduction System -- Surgical Anatomy of the Aorta -- Appendix. .
Keywords: Medicine; Human anatomy; Heart -- Surgery; Endoscopic surgery; Thoracic surgery; Vascular Surgery; Medicine & Public Health; Cardiac Surgery; Vascular Surgery; Thoracic Surgery; Minimally Invasive Surgery; Anatomy